Nivel de incidencia de la aplicación de los juegos infantiles en la formación integral de los niños y las niñas de los jardines de infantes Luz de Amércia, Eulogio Serrano Armijos, David Rodas Cuervo, Cruz Ramírez de Cruz, Fulton Franco Cruz, Paraíso de los Niños, y Nueva Semillita, del cantón Machala, periodo 2010-2011. - Bazaran Sucal, Johana del Cisne (2013)
the purpose of this investigation is considered to improve educational conditions of the children in the kindergartens. Light of America, Eulogio Serrano Armijos, David Rhodes Cuervo, Cruz Ramirez Cruz, Fulton Franco Cruz, Children's Paradise and New Semillita city of Machala, province of El Oro, especially to hone your senses, to acquire greater mastery of his body, abstraction and generalization. This worked is based on the theories of game proposed, autonomic and practical learning, the teacher is the stimulatory capacities of the learners, the teaching-learning process, go stimulated with the game, where the student learns how important and useful with the mediation of the teacher.